The power of identification schemes. (7th February 2008) - Kurosawa, Kaoru; Heng, Swee-Huay
In this paper, we show that Identification schemes (ID-schemes) are very powerful in some areas of cryptography. We first prove an equivalence between non-interactive trapdoor commitment schemes and a natural class of ID-schemes. We next propose a more efficient online/off-line signature transformation than Shamir-Tauman. As an application, we present a variant of the Boneh-Boyen (BB) signature scheme which is not only online/off-line but also has a smaller public key size than the original BB scheme. Finally, we present the first Identity-based ID-scheme which is secure against concurrent man-in-the-middle attack without random oracles by using our variant of BB signature scheme.